2019
DOI: 10.5430/ijfr.v10n5p450
|View full text |Cite
|
Sign up to set email alerts
|

Investor Sentiment and Firm Financial Performance of Malaysian IPO Firms: Pre and Post Financial Crisis

Abstract: The main purpose of this study is to investigate an important issue in behavioural finance area that is the role of investor sentiment in determining firm performance, alongside with market timing and other fundamental firm factors in the context of Malaysian market. The impact of pre and post financial crisis during study period of 2004 to 2015 is incorporated in the analysis. The study uses a balanced panel data of 143 IPO firms in Malaysia during the study period. The sentiment index is developed using pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019). Therefore, behavioural economics holds in the Nigerian context.…”
Section: Conclusion and Recommendationssupporting
confidence: 67%
See 2 more Smart Citations
“…This result agrees with studies that found significant positive relationship between investors' sentiment and stock performance among emerging and developing countries (Dalika &Yudhvir, 2015;Asian Naik & Padhi, 2016;Alajekwu, Obialor, Okoro & Ibenta, 2017;Aggarwal, 2017;Pandey & Sehgal, 2019;Cheng, 2019). On the other hand, the finding from this study disagrees with studies that found no significant relationship between investors' sentiment and stock trading (Zainudin, Zaki, Hadi, Hussain & Kantakji, 2019). Therefore, behavioural economics holds in the Nigerian context.…”
Section: Conclusion and Recommendationssupporting
confidence: 67%
“…These studies corroborate findings from Alajekwu, Obialor, Okoro and Ibenta (2017) which found that sentiment significantly influences market performance in Nigeria. On the other hand, some empirical studies found no evidence among developing and emerging economies (Zainudin, Zaki, Hadi, Hussain &Kantakji, 2019). Thus, the study on investors' sentiment and stock performance among emerging and developing economies remains inconclusive.…”
Section: 0mentioning
confidence: 98%
See 1 more Smart Citation
“…These practices involve a firm's commitment to environmental preservation, corporate social responsibility, and good governance. They include initiatives to reduce resource consumption, limit environmental emissions, sustain human rights, improve employment standards, engage with communities, and establish strong internal and external governance mechanisms (Kalia & Aggarwal, 2023;Yoon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of mixed results, global financial crises, and decreased trust from stakeholders has created the need for reforms aimed at enhancing ESG practices. (Kalia & Aggarwal, 2023;Yoon et al, 2018). Similarly, Chen et al (2021) propose that ESG investment initially triggers a "Substitution Effect", resulting in a short-term adverse impact on FP.…”
Section: Introductionmentioning
confidence: 99%